Developing a Bahasa Indonesia Teaching Module on Character and Characterization Based on the Traditional Folktale Rokat Pandhâbâ to Enhance Fourth-Grade Students’ Reading Skills - Amirotudz Dzofiroh; Priyono Tri Febrianto (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This study aimed to develop and examine the effectiveness of an Indonesian language teaching module based on the traditional folklore in improving fourth-grade students’ reading comprehension skills, particularly in identifying characters and characterization. The scope of the study focused on the development of contextual teaching materials that integrate local Madurese cultural values into Indonesian language learning. The research employed a Research and Development (R&D) method using the instructional design model, which included needs analysis, design, development, expert validation, field testing, and evaluation stages. The participants consisted of 18 fourth-grade students of SDN Bugih I Pamekasan. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and learning achievement tests in the form of pretests and posttests. The module was developed by integrating the PQ4R learning model (Preview, Question, Read, Reflect, Recite, Review) to enhance students’ cognitive and metacognitive engagement in reading activities. The results showed that the developed module achieved a very good level of feasibility based on expert judgments and positive student responses. The students’ average score increased from 60.22 in the pretest to 81.94 in the posttest. Statistical analysis using the Wilcoxon Signed Rank Test indicated a significant difference in learning outcomes, with Asymp. Sig. (2-tailed) < 0.05. It can be concluded that the -based teaching module is effective in improving students’ reading comprehension skills and fostering appreciation of local culture.